Screening for Hypertension in Obese Adolescents using Ambulatory Blood Pressure Monitoring - Muhammad Nadeem Khan, Saeed Maqsood, Muhammad Saad Jibran, Atta Ullah Khan, Muhammad Rafiq Khan, Jalil Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Obesity in adolescents is associated with an increased risk of hypertension, which may remain undiagnosed using conventional office blood pressure (OBP) measurements. Ambulatory blood pressure monitoring (ABPM) provides a comprehensive assessment of blood pressure patterns over 24 hours, capturing daytime and nighttime variations, and identifying masked or white coat hypertension. Objective: To evaluate the effectiveness of ABPM in screening for hypertension among obese adolescents in a tertiary care hospital. Methods: A cross-sectional study was conducted at the Department of Cardiology Medical Teaching Institution Bannu, Department of Cardiology DHQ Teaching Hospital MTI DI Khan, department of pediatrics Medical Teaching Institution, Bannu and Department of Medicine Pak International Medical College Peshawar, from September 2021- Feb 2022, enrolling 100 obese adolescents aged 12–18 years. Baseline demographic data and body mass index (BMI) were recorded. Office blood pressure measurements were taken using a standardized protocol, followed by 24-hour ABPM. Blood pressure readings were analyzed for average daytime, nighttime, and 24-hour values, nocturnal dipping status, and prevalence of masked or white coat hypertension. Data were analyzed using SPSS, with p<0.05 considered statistically significant. Results: Among participants, 18% had elevated office blood pressure, while ABPM detected hypertension in 30%. Masked hypertension and white coat hypertension were observed in 8% and 5% of participants, respectively. Non-dipping nocturnal patterns were identified in 20% of adolescents. Male participants had slightly higher prevalence of hypertension compared to females (32.8% vs. 26.2%), though this was not statistically significant. ABPM revealed blood pressure patterns not captured by office measurements, emphasizing its diagnostic superiority. Conclusion: ABPM is an effective tool for detecting hypertension and abnormal blood pressure patterns in obese adolescents. Routine use of ABPM can facilitate early identification and intervention, reducing long-term cardiovascular risk. Keywords: Obesity, Adolescents, Hypertension, Ambulatory Blood Pressure Monitoring